PENERAPAN SANKSI PIDANA TERHADAP ANAK PELAKU TINDAK PIDANA PEMBUNUHAN - Meryl Fernanda (2021)
Deviation from values, norms, and laws by children are called juvenile delinquency. The application of children's law must be distinguished from the application of adult law, because children are the nation's next generation who should be protected, guarded, and educated in order to create a good generation. On the one hand, children need to receive protection, but on the other hand, children who have committed criminal acts must be held accountable. This research focuses on the application of criminal sanctions against the perpetrators of murder committed by children and the things that mitigate the criminal sanctions for murder by children. Researchers used normative juridical research methods, namely using secondary data in the form of primary legal materials for example Laws, on secondary legal materials for example books, journals and theses and tertiary legal materials such as legal dictionaries.